Stress to Human Health Due to Electromagnetic Radiation Emitted from Mobile Phone - Ganguly, S.; Mukhopadhayay, S. K.; Guha, S. K. (International Journal of Bio-resource and Stress Management, 2011)
Electromagnetic radiations are being used by mobile phones and it is being believed that these rays are harmful to both human and animal health. Studies on the hazardous effect of mobile phone are the subject of recent interest. This has also got a boost due to the enormous increase in mobile phone usage across the globe in recent past. Many other digital wireless systems like data communication networks produce similar kind of radiations. Users must be educated and awareness is needed to be created regarding the hazardous and ill effects of use of mobile phones and other wireless communications in human society.